2021
DOI: 10.1037/cdp0000339
|View full text |Cite
|
Sign up to set email alerts
|

Racism and preparation for bias within African American families.

Abstract: Objectives: Exposure to racism experienced by caregivers poses a threat to child developmental outcomes. The current study examines the effects of caregiver-experienced racism on the development of internalizing behaviors for African American children during a sensitive period in their development of racial awareness. Two aspects of caregiver-provided ethnic racial socialization (ERS), cultural socialization and preparation for bias, were assessed as moderators. Supported by prior research, cultural socializat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The differential outcomes in the preparation for bias literature may potentially be a result of the fact that these messages can be more complex and require more parental skills (e.g., emotion regulation and empathy). Preparation for bias messages are also contingent upon parents’ own experiences with racism (Osborne et al, 2020). Parents struggle with how to provide balanced messages that attend to developmental readiness, build skills to cope with discrimination, and do not overinflate distrust for other groups (Hughes et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The differential outcomes in the preparation for bias literature may potentially be a result of the fact that these messages can be more complex and require more parental skills (e.g., emotion regulation and empathy). Preparation for bias messages are also contingent upon parents’ own experiences with racism (Osborne et al, 2020). Parents struggle with how to provide balanced messages that attend to developmental readiness, build skills to cope with discrimination, and do not overinflate distrust for other groups (Hughes et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The transition of childhood-adolescence to young adulthood is challenging for many individuals, especially Black youth, because they may no longer have the family protections that might have shielded them from racism. Surprisingly, young BIPOC adults whose families prepared them for bias and discrimination have been found to have more depressive symptoms than young adults whose parents did not openly discuss race or racism, perhaps a protective parental act [52][53][54]. In a study of Black women in Detroit, MI, the authors reported an association between a change in the frequency of discrimination over time and the change in depressive symptoms over time [23].…”
Section: Discussionmentioning
confidence: 98%
“…In Brown et al’s (2016) development of a measure of gendered racial-ethnic socialization, multiple forms of gendered racial socialization were identified. Extending previous work on racial socialization investigating the intersection of message types (e.g., Osborne et al, 2021), in this study, we explore the interplay between two forms of gendered racial socialization (internalized gendered racial oppression [IGRO] and gendered racial pride and empowerment [GRPE]; Brown et al, 2016), and how their interplay affects the mental health (depression, anxiety, and stress) of Black adolescent girls.…”
Section: Racism’s Impact On Black Youth: Psychosocial Consequences An...mentioning
confidence: 99%